(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
cultural anthropology is a scientific field that studies the cultural aspects of humanity. It analyzes cultural elements of different peoples such as customs, traditions, language and art. Cultural anthropologists also study other aspects of culture, such as social structures, religion, economics, and politics. The field helps to understand the cultural diversity of humanity, to identify connections between different cultures, and to analyze cultural change. Cultural anthropology, through ethnographic research, provides a deeper understanding of people’s way of life and their worldview. The main goal of cultural anthropology is to study the processes of how culture is formed, developed and transformed. The field also analyzes modern processes such as globalization, migration and cultural exchange.